Using Of Teleconference As A Medium To Establish An “E-Global-Learning-System”: An Experience Of 1000guru-Association On Facilitates Open And Distance Learning Activities With Schools In Indonesia - HARIS, Ikhfan (The Turkish online journal of distance education TOJDE, 2014)
Information communication and technology (ICT) has been used in various fields. The use of teleconference for teaching and learning activities is currently not a new topic in global world. In Indonesia, through IMHERE Program from Directorate of Higher Education, some universities have been connected with a network of teleconference as a medium of disseminate knowledge. However, when compare to university, the use of teleconference is not yet well-known in schools in Indonesia. This paper aims at presenting the experiences on the use of Teleconference as a medium of teaching secondary school pupils new information on different subjects they discovered in international learning environment. This activity is carried out by Indonesian students who study abroad e.g. students who study in Germany, Japan, Canada, Australia and USA. This paper will also analyse the feedback from the beneficiaries of the teleconference program, to gather opinion about the prospect, challenges in the administration, organisation, and the pedagogy implication of the use of information communication and technology in schools in Indonesia. The author will also give suggestions or recommendations on the best strategies of improving the use of information technology in schools. This is important to further promote and establish the e-Global-learning-system in Indonesia.